Of the teachers, by the teachers, for the teachers - The 7Cs Framework of (English) Grammar for Practical, Pedagogical Purposes - Deak Kirkham; Milada Walková, FHEA (Journal of Linguistics and Language Teaching)
Despite the existence of a range of grammatical theories, few are designed for, nor are broadly well understood by, the language teaching field. The field itself, moreover, has adopted various approaches to teaching grammar as well as variant terminologies both for grammatical notions (such as subject or agent) and for certain grammatical constructions (such as phrasal verb or compound noun). While recognising the value of this diversity, we propose a seven-point framework for teaching grammar, named the 7Cs. The 7Cs consists of categories, combinations, components, concepts, correlations, connections and contexts. Between them, these 7Cs cover all pedagogically relevant aspects of the grammar from formal considerations through to pragmatic and contextual issues. In addition to offering a standardised terminology and annotational techniques, the 7Cs framework offers sufficient capacity to capture the complexities of various structures. The framework is presented with pedagogical rationales after which it is exemplified in application to the passive voice.